REGULARITIES OF SPACE TIME DISTRIBUTION OF EARTHQUAKES ON THE TERRITORY OF ARARAT SEISMIC POLYGON (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
To study the peculiarities of seismic regime of the territory of Ararat seismic polygon analysis of M ≥ 2.5 earthquakes that occurred between 1962 and 2012 was performed using the catalog of the Seismic Protection Survey of the Ministry of TA and ES of RA. The territory within 70 km radius from Yerevan was studied.
Keywords: seismic regime; Gutenberg–Richter frequency graph; $b$ constant; cumulative quantity of earthquakes; Ararat seismic polygon